The Hippocratic treatise On glands - Hippocrates.; Craik, Elizabeth M. (Studies in Ancient Medicine, 2009)
This is a new edition, with translation, introduction and commentary, of the Hippocratic treatise On Glands . Through a close analysis of both content and expression, the text is interpreted and situated in the wider context of ancient medical writing.